Simulating the studio: how designers orchestrate ai across ux and product workflows - Gnatovych, V. (ТОВ «Видавництво Ліра-К», 2025)
This article explores the shift in UX and product design from manual execution to AI orchestration. Through a reflexive case study, we examine how solo designers use tools like ChatGPT, Perplexity, and Claude to simulate multidisciplinary studios. Findings show 60% faster creative output alongside challenges in governance and equity. A roles-and- tools framework is presented that positions design orchestration within the broader AI augmentation paradigm, distinct from replacement narratives.
Keywords: UX; AI